A Proximal Algorithm with Bregman Like Distances to Equilibrium Problems with Quasimonotone Bifunctions in Hilbert Spaces - Papa Quiroz, Erik A. (2022)
The paper introduces a proximal point algorithm for solving equilibrium problems on convex sets with quasimonotone bifunctions in Hilbert spaces using Bregman distances. Supposing appropriate hypothesis on the model, this paper proves that the sequence of points which are generated for the algorithm converges weakly to certain solution point of the equlibrium problem.